Fruit and vegetable consumption among adolescent secondary school students in Boukombe and Natitingou, North Benin - Houndolo, Melina Maureen; Houndolo, Sam; Jordan, Irmgard; Majaliwa, Elianna; Koukou, Elie; Ngianga-Bakwin, Kandala; Azandjeme, Colette; Katsivo, Melanie Nyambura; Termote, Céline; Hounkpatin, Waliou Amoussa (MDPI, 2025)
Fruit and vegetables (F&V) are recommended for a healthy life. Adolescence is a critical period for the onset of eating disorders and future health. F&V consumption among adolescents is globally low, making this group a key target for diet/nutrition-related interventions. This cross-sectional study aimed to assess F&V consumption among secondary school students in the food-insecure communes of Boukombe (rural) and Natitingou (urban), Benin. Using probabilistic random sampling, 303 students completed F&V intake frequency questionnaires and 24-h dietary recalls on school and non-school days. Poisson models identified factors associated with F&V consumption. The results showed that only 8.8% (Boukombe) and 11% (Natitingou) of students consumed fruit at least twice per day, and over 80% of students had not eaten fruit in the preceding 24 h; 9.9% and 11.4%, respectively, consumed vegetables at least twice per day. On average, 45.5% of students in Boukombe and 68% in Natitingou consumed at least three types of vegetables on school days. The most commonly consumed fruits were oranges in Boukombe and lemons in Natitingou. Factors influencing fruit consumption included sex (p = 0.005), age (p = 0.04), and mothers’ occupation (p = 0.03) on school days/and school or non-school days, while commune (p = 0.00017) and ethnic group affected vegetable consumption. Such low F&V consumption among surveyed students is a matter of public health concern, as it is likely to affect their health―in terms of micronutrient deficiency―and intellectual performance. These results should incentivize nutrition researchers, project managers, public health officials, and policymakers to (re)design and implement broader measures targeting secondary school students’ dietary practices to increase their F&V consumption.